2007
DOI: 10.1183/09031936.00128706
|View full text |Cite
|
Sign up to set email alerts
|

The effects of hypoxia on the cells of the pulmonary vasculature

Abstract: Pulmonary hypertension is associated with remodelling of pulmonary vessels. Chronic hypoxia is a common cause of pulmonary hypertension and pulmonary vascular remodelling. Vascular remodelling is characterised largely by fibroblast, smooth muscle and endothelial cell proliferation, which results in lumen obliteration. Chronic hypoxia elicits expression of mitogens, growth factors and cytokines by fibroblasts and endothelial cells, and also the suppression of endothelial nitric oxide synthase. Although hypoxic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
150
0
1

Year Published

2009
2009
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 198 publications
(155 citation statements)
references
References 87 publications
4
150
0
1
Order By: Relevance
“…Chronic hypoxia induces structural changes to the pulmonary arteries including the appearance of SMC-like myofibroblasts expressing α-SMA, in previously nonmuscularized vessels. While hypoxia-induced remodeling is associated with medial hypertrophy, direct stimulation of SMC proliferation by hypoxia remains somewhat controversial (37). Although there are reports of hypoxia driven smooth muscle cell proliferation (38,39), several in vitro studies have shown that hypoxia does not directly increase SMC proliferation (40)(41)(42) or may actually decrease proliferation (43,44).…”
Section: R E S E a R C H A R T I C L E M O L M Ementioning
confidence: 99%
“…Chronic hypoxia induces structural changes to the pulmonary arteries including the appearance of SMC-like myofibroblasts expressing α-SMA, in previously nonmuscularized vessels. While hypoxia-induced remodeling is associated with medial hypertrophy, direct stimulation of SMC proliferation by hypoxia remains somewhat controversial (37). Although there are reports of hypoxia driven smooth muscle cell proliferation (38,39), several in vitro studies have shown that hypoxia does not directly increase SMC proliferation (40)(41)(42) or may actually decrease proliferation (43,44).…”
Section: R E S E a R C H A R T I C L E M O L M Ementioning
confidence: 99%
“…We speculate that chronic proliferative activity is involved in the thickening of the media wall and pulmonary arterial stenosis. Hypoxia could act on fibroblasts and endothelial cells to trigger PASMC proliferation (29). These adjacent cells with PASMCs can release many growth factors for PASMC proliferation such as PDGF, FGF-2, and EGF (30 -32).…”
Section: +mentioning
confidence: 99%
“…The established model of PH in the course of DPLD was the one related to vascular remodeling due to interstitial pathology and/or hypoxia [3]. Nevertheless, the presence of vascular pathology in the areas of minor interstitial lung disease, and the occurrence of PH in the early stage of disease in patients without substantial hypoxemia, indicate the more complex pathogenesis.…”
Section: Pathobiology Of Ph In the Course Of Dpldmentioning
confidence: 99%